Preparação e caracterização de biomateriais poliméricos para avaliação da viabilidade de uso como phantom biológico - Ferreira, Irisnei Luzia (2016)
The theoretical and experimental developments in the biomaterials area have been directly applied to different fields of Medicine (odontology, regenerative medicine and radiotherapy). These advances have focused both for diagnosing diseases such as for quantifying degrees of progression. From the perspective of these studies, biomaterials are being designed and manufactured for application in various areas of science, provided advances in diagnostic radiology, radiotherapy dosimetry and calibration of radiotherapy equipment. Develop a phantom from a biomaterial has become a great ally of medicine in the treat patients with oncological diseases, allowing better performance of the equipment in order to reduce damage to healthy tissue due to excessive exposure to radiation. This work used polymers: chitosan and gelatin, for making the polymeric structures and controlled for different types of production and processing, characterizing and evaluating the biopolymer by physical techniques (STL, SEM and DEI) and therefore analyze applicability as phantom mouse lung. It was possible to evaluate the morphology of biomaterials quantitatively by scanning electron microscopy associated with imaging technique. The relevance of this work focuses on developing a phantom from polymeric biomaterials that can act as phantom providing high image contrast when subjected to analysis. Thus, the choice of DEI technique is satisfactory since it is an imaging technique of X-ray high resolution. The images obtained by DEI have shown the details of the internal microstructure of the biomaterial produced which have ≈ 10 μm dimension. The phantoms had made density ranging from 0.08 a 0.13 g/cm3.